The Ability of Students of SMAN 4 Kota Sukabumi Towards English TKA - Mutia Zahara; Otong Setiawan Djuharie (Jurnal Ilmu Sosial dan Humaniora, 2026)
English plays a crucial role in academic and professional fields, making the assessment of students English proficiency increasingly important. In Indonesia, the government has introduced the Tes Kemampuan Akademik (TKA) as a standardized assessment to measure students academic abilities. This study aims to examine the ability of students at SMAN 4 Kota Sukabumi toward the English TKA, focusing on language aspects such as reading comprehension, vocabulary, grammar, and students perceptions of the test. This research employed a qualitative descriptive method. Data were collected through a questionnaire distributed via Google Form to twelfth-grade students of SMAN 4 Kota Sukabumi during the 2024/2025 academic year. The questionnaire used a Likert scale and open-ended responses to explore students experiences, perceived difficulties, and attitudes toward the English TKA. The findings show that most students perceive English TKA as more difficult than regular school examinations, particularly in the reading section due to time management issues. Vocabulary was generally not considered a major obstacle. However, students reported insufficient guidance and specific strategies from teachers in preparing for the English TKA. Despite these challenges, the majority of students agreed that English TKA effectively measures their overall English proficiency and motivates them to study English more seriously. In conclusion, English TKA is perceived as a relevant and comprehensive assessment tool. Greater instructional support and strategic preparation are needed to improve students readiness and performance.